(untitled) (Research, Society and Development, 2021)
This article sought to highlight the possibilities for an educational practice that would enhance the understanding of knowledge. It is believed that concept maps are a metacognitive device that gives meaning to teaching and learning, raising, and building knowledge. In this way, the objective was to identify the proposals about meaningful learning formulated by David Ausubel and Joseph Novak’s theory of education, from the development of the concept map theory as a teaching-learning strategy and student assessment in integrated secondary education in agriculture at the Bambuí campus of the IFMG. Thus, the method of this study had as an approach a qualitative-quantitative research, considering the exploratory-descriptive type in a case study, and the data were taken from a directed activity and a questionnaire applied to students, which provided the data analysis with the help and use of the Microsoft Office Excel® 2021 software and the R statistical program (R CORE TEAM, 2021). The results obtained in the research followed the perception that concept maps are favorable for teaching that values significant learning, if the nuances permeated by the student’s conditions are considered. In such a way, it is concluded that the effectiveness in the pedagogical action permeates different processes, and thus, one must engage in the reflection of the pedagogical practices.